Distribution, Morphological Characterization, and Resiniferatoxin-Susceptibility of Sensory Neurons That Innervate Rat Perirenal Adipose Tissue - Liu, Bo-Xun; Qiu, Ming; Zong, Peng-Yu; Chen, Xu-Guan; Zhao, Kun; Li, Yong; Li, Peng; Sun, Wei; Kong, Xiang-Qing (Frontiers in Neuroanatomy, 2019)
Perirenal adipose tissue (PrAT) is a visceral adipose tissue involved in the pathogenesis of obesity and cardiovascular diseases via neural pathways. However, the origins, morphological characterization, and resiniferatoxin (RTX)-susceptibility of sensory neurons that innervate rat PrAT are yet unclear. Using neural tracing, an injection of DiI (1,1'-dioctadecyl-3,3,3',3'-tetramethylindocarbocyanine perchlorate) into PrAT revealed that sensory neurons that innervate PrAT reside in T9-L3 dorsal root ganglia (DRG). Peak labeling occurred in T13 and L1 DRGs. Two distinct peaks were observed in cross-sectional areas of the labeled soma, and the mean cross-sectional area was 717.1 ± 27.7 μm2. Immunofluorescence staining for transient receptor potential cation channel subfamily V member 1 (TRPV1) separated DiI-positive neurons into three subpopulations: small TRPV1-negative, small TRPV1-positive, and large TRPV1-negative. Furthermore, the injection of RTX into PrAT reduced labeled cells by 36.7% where TRPV1-positive cells were the main target of RTX denervation. These novel findings provide a structural basis for future TRPV1-dependent and TRPV1-independent studies on the sensory innervation of PrAT, which may be of interest for future therapeutic obesity treatment and intervention.